Analysis of the Influence of Product Knowledge, Attitude, and Halal Certification on Purchase Intention in Halal Food Products - Yulinda Tarigan; Vivian Aldama Z (Journal of Applied Business Administration, 2023)
This research aims to determine the effect of product knowledge, attitude and halal certification on purchase intention in halal food products at five universities in Batam City. This research uses a quantitative approach, descriptive statistical data analysis techniques and multiple linear regression analysis. The sample in this research amounted to 370 respondents. Data collection techniques in this research using a questionnaire through google form. The population in this research were business management students from five universities in Batam city with a sample of 370 respondents. The results of this research indicate that product knowledge has a positive and significant effect on purchase intention which can be proven by the value of t count > t table that is 3.779 > 1.99647, attitude has a positive and significant effect on purchase intention with t count 3,527 > t table 1.99647, and halal certification has a positive and significant influence on purchase intention where t count > t table is 3,220 > 1.99647. In addition, the three independent variables of product knowledge, attitude and halal certification have a positive and significant influence simultaneously on purchase intention where the value of Fcount 46.109 > Ftable 2,63.